PEMBUATAN STRIP TEST DAN IDENTIFIKASI FENILBUTAZON PADA JAMU PEGAL LINU - Henny Nurhasnawati; Triswanto Sentat; Adi Prasetiyo (Jurnal Ilmiah Manuntung, 2020)
Jamu (Indonesian herbal medicine) are prohibited from containing chemicals medicine which are isolated or synthetic chemical compounds. Chemical compounds which is commonly added in jamu pegal linu (rheumatic pain) is phenylbutazone. One simple alternative test for detecting chemicals medicine content is to use a strip test. The purpose of this study was to determine the presence or absence of phenylbutazone content in jamu using a strip test. The research conducted is experimental research. This study used 6 samples of jamu pegal linu which were extracted using 95% ethanol solvent. The strip test is carried out by immobilizing reagents into Whatman’s filter paper using the impregnation method. Data obtained from observations of the color change of the strip test. The results showed that strip test made with alizarin red reagent and potassium hexacyanoferate (III) identified 2 samples of jamu pegal linu containing phenylbutazone, namely sample D and E, from 6 samples that circulated in Sungai Pinang District, Samarinda.